Dietary habits and lifestyle practices among normal and overweight undergraduate students in Universiti Sains Malaysia, Health Sciences Campus, Kubang Kerian - Zukhi, Nurul Alis Farhana Mohd (Universiti Sains Malaysia, 2024)
Young adults' dietary habits and lifestyle practices have been remarked as the prime cause of being overweight, influenced by several factors such as personal choices, society, and the environment. The dietary habits of young adults are characterized by a tendency to skip meals, especially breakfast, frequent consumption of snack foods or drinks, and repeated attempts at dieting due to preoccupation with body image and appearance. Although the onset and development of dietary habits and lifestyle practices are mostly apparent during childhood, university students also undergo a critical period where changes in their behaviors often result in weight gain. The main objective of this research is to assess the dietary habits and lifestyle practices among normal and overweight undergraduate students at Universiti Sains Malaysia, Health Sciences Campus (USM), Kubang Kerian. This cross-sectional study involved 110 undergraduate students from the Health Sciences Campus (USM), Kubang Kerian, Kelantan, Malaysia. A self-administered questionnaire was distributed online to selected respondents via Google Forms which covered parameters such as dietary habits, lifestyle practices as well as knowledge and perceptions about dieting, balanced nutrition, and self-body image . The results indicated that both BMI categories exhibited similar dietary habits and lifestyle practices, but there were significant differences in their food choices, meal frequency, and responses to stress. Using Pearson’s chi-squared test, there was no significant association (p>0.05) between gender and their BMI category. The study's findings provide detailed information about the dietary habits and lifestyle practices among normal and overweight undergraduate students at the Health Sciences Campus.